PERAN GURU BK DALAM MENGATASI KONFLIK PERTEMANAN ANTAR SISWA DI SMA NEGERI 1 KOTA BENGKULU - Saputri, Jalenchia Darin; Hardianti, Susi; Ariani, Winda Ade (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
The aim of this research is to describe friendship conflicts that often occur, identify the factors that cause conflicts between students and describe the role of guidance and counseling teachers in overcoming friendship conflicts between students. Data collection was carried out through observation, interviews and documentation. Research findings show that the conflicts that occurred at SMAN 1 Bengkulu City included personal, group, academic and interpersonal conflicts. Factors that cause conflict are poor communication, misunderstandings, differences of opinion, and lack of skills managing conflict. The role of guidance and counseling teacher is very important in handling student friendship counflicts because the guidance and counseling teachers can act as a mediator and guide. They help students understand each other’s perspectives and teach conflict resolution skills.